Methionine synthase polymorphisms frequencies distribution in the Jordanian population - Farra, Helmi Yousif AL (Journal of Pediatric Neurology, 2011)
The main purpose of this study was to determine the frequencies distribution of methionine synthase (MTR) (MTR 2756 A > G and MTR 2758 C > G) polymorphisms in the Jordanian population. The frequencies of these polymorphisms were determined in a sample of 491 individuals (males were 270 and females were 221) collected from all the Jordanian regions, which is a good representation of the Jordanian population. The different alleles and genotypes at the two polymorphic sites were identified using the polymerase chain reaction-restriction fragment length polymorphism polymerase chain reaction restriction fragment length polymorphism analysis. Results showed that the overall percentages in the whole Jordanian population were 90.73% and 9.27% for the MTR 2756 A and MTR 2756 G alleles respectively. Only the wild type allele (C) of the MTR 2758 C > G polymorphism was detected. In addition, the association of MTR 2756 A > G and MTR 2758 C > G polymorphisms with the development of neural tube defects (NTDs) was examined using 17 cases of mothers from the Northern part of Jordan who gave birth to NTD affected children during the period of this study. Results showed no association between these two examined polymorphisms and the increase in maternal risk for giving birth to NTD children. The results in this study recommend that more examination should be done on larger populations to make good conclusion, also more studies on gene-gene interaction should be done to examine the associations with NTDs.
Keywords: Neural tube defects; methylenetetrahydrofolate reductase; methionine synthase; polymorphism; Jordan